Ethical and Legal Challenges of Artificial Intelligence in the Judicial System: An Indonesian Perspective - Hidayat, Wahyu; Muis, Abdullah (Lembaga Publikasi Ilmiah Nusantara, 2025)
The integration of Artificial Intelligence (AI) into the judicial system has introduced significant opportunities for enhancing efficiency, accuracy, and access to justice. However, it also raises complex ethical and legal challenges, particularly in developing countries such as Indonesia. This study examines the implications of AI adoption in the Indonesian judicial system by focusing on issues of accountability, transparency, fairness, data privacy, and potential bias in algorithmic decision-making. Using a normative juridical approach supported by literature review and analysis of existing regulations, this research highlights the absence of comprehensive legal frameworks governing AI use in judicial processes, which may undermine the principles of due process and the independence of the judiciary. Ethical concerns, such as the risk of dehumanization of justice and the erosion of judicial discretion, further complicate AI implementation. The findings suggest that Indonesia requires a robust regulatory and ethical framework to balance technological innovation with the protection of fundamental rights. This study contributes to ongoing global debates on responsible AI governance in the justice sector and offers recommendations for policy formulation tailored to the Indonesian legal context.